The Effects of Different Signaling Pathways in Adenylyl Cyclase Stimulation on Red Blood Cells Deformability - Semenov, Alexey N.; Shirshin, Evgeny A.; Muravyov, Alexei V.; Priezzhev, Alexander V. (Frontiers in Physiology, 2019)
Signaling pathways of red blood cells (RBC) micromechanics regulation, which are responsible for maintaining the microcirculation, constitute an important property of RBC physiology. Selective control over these processes may serve an indispensable tool for correction of hemorheological disorders, which accompany a number of systemic diseases (diabetes mellitus I&II, arterial hypertension, malaria, etc.). Namely, activation of certain pathways involving adenylyl cyclase may provide fast adaptive regulation of RBC deformability (RBC-D). However the specific molecular conditions of intracellular signal transduction in mediating RBC microrheological properties at adenylyl cyclase stimulation remain unclear. In this paper we present the results of the in vitro study of the effects of different signaling pathways in adenylyl cyclase stimulation on RBC-D. We studied (1) direct stimulation of adenylyl cyclase with forskolin; (2) non-selective adrenoreceptor stimulation with epinephrine; (3) β2-adrenoreceptor agonist metaproterenol; (4) membrane permeable analog of cAMP (dibutyryl-cAMP). Using laser ektacytometry we observed a concentration-dependent increase in RBC-D for all studied effectors. The EC50 values for each substance were estimated to be in the range of 1-100 µM depending on the shear stress applied to the RBC suspension. The results can serve as an evidence of adenylyl cyclase signaling cascade involvement into the regulation of RBC micromechanical properties presenting a complex molecular pathway for fast increase of microcirculation efficiency in case of corresponding physiologic metabolic demands of the organism, e.g. during stress or physical activity. Further studies of this molecular system will reveal new knowledge which may improve the quality of medical treatment of hemorheologic disfunctions.